THE ROLE OF LEARNERS’ TEST PERCEPTION IN CHANGING ENGLISH LEARNING PRACTICES: A CASE OF A HIGH-STAKES ENGLISH TEST AT VIETNAM NATIONAL UNIVERSITY, HANOI - Lan, Nguyen Thuy; Nga, Nguyen Thuy (VNU Journal of Foreign Studies; Vol 35 No 6DO - 10.25073/2525-2445/vnufs.4481, 2020)
Among various factors influencing foreign language learning, learners’ perception of a high-stakes language test plays a crucial part, especially when the test serves as a threshold for their university graduation.  In this study, the researcher tested a washback effect model by focusing on test-takers’ perception of the high-stakes test VSTEP in terms of test familiarity, test difficulty and test importance. On a sample of 751 Vietnamese learners of English at Vietnam National University, structural equation model was employed to validate the conceptual model. The analytical methods of Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) were used for analysis. Our empirical findings revealed that VSTEP seems to have had a pervasive impact on the participating students. Senior students’ evaluations of VSTEP acted as the largest factor in constituting the participants’ perception of VSTEP. There are positive links between test pressure and test familiarity with students' goal setting and study planning as well as their selection of learning content and materials. Meanwhile, the pressure from the test had no effect on students’ seeking opportunities to practice with foreigners, and test familiarity did not influence students’ choice of study methods and exam preparing strategies. The emerging patterns from the data also suggested that participating students preferred test-oriented learning content and activities at the cost of interactive English practices for real-life purposes.